Photonic Devices with Siloxane Membranes - Matej Goraus; Lubos Suslik; Dusan Pudis; Jana Durisova; Daniel Jandura; Jaroslav Kovac; Marek Tlaczala (Communications - Scientific letters of the University of Zilina, 2017)
Expansion of polymer nanotechnologies accelerated the polymer photonics. This technology brings novel interesting results with simple and cheap solutions. Promising candidates are siloxane materials as polydimethyl siloxane (PDMS) and polydimethyldiphenyl siloxane (PDMDPS) with unique mechanical and optical properties. In this paper we present laser lithography technologies in a combination with siloxane embossing for fabrication of different grating structures with periodical and quasiperiodical symmetry. We present the concept of siloxane based thin membranes with patterned surface as an effective diffraction element for modification of radiation pattern diagram of light emitting diodes (LEDs) and enhancement of angular detection properties of photodiodes. Also the combination of PDMDPS and PDMS was used for fabrication of a waveguide structure with surface relief Bragg grating. Optical properties of fabricated LEDs are investigated by near- and far-field measurements. Transmission properties of fabricated waveguide are investigated by optical spectrum analyzer.